Inhibition of demineralization in vitro around amalgam restorations - Pimenta, Luiz André Freire; Fontana, Ueide Fernando [UNESP]; Cury, Jaime Aparecido; Serra, Mônica Campos; Elderton, Richard J. (My University, 1998)
Objective: The purpose of this in vitro study was to evaluate some forms of preventing or avoiding demineralization within enamel cavity walls adjacent to amalgam restorations. Method and materials: Third molar teeth were sectioned to obtain 72 specimens, divided into one control and five experimental groups: amalgam only; varnish plus amalgam; acidulated phosphate fluoride plus amalgam; adhesive amalgam; glass-ionomer cement plus amalgam; control (amalgam only, not subjected to a demineralization challenge). The experimental groups were subjected to pH and thermal cycling and then submitted to enamel hardness determinations. Results: Significant differences between the treatment groups revealed that the bonded amalgam technique offered the best resistance to demineralization. The use of cavity varnish resulted in greater mineral loss than amalgam placed alone. Conclusion: The use of an adhesive system, glass-ionomer cement, or acidulated phosphate fluoride under amalgam restorations may interfere with development of secondary caries.
Keywords: Amalgam restoration; Bonded amalgam restoration; Demineralization; Microleakage; Secondary caries; acidulated fluorophosphate; biomedical and dental materials; copalite; dental alloy; dispersalloy; glass ionomer; Panavia EX; phosphate; Photac Bond; Photac-Bond; plant resin; resin cement; chemistry; comparative study; dental bonding; dental caries; dental surgery; enamel; hardness; human; methodology; molar tooth; tooth disease; Acidulated Phosphate Fluoride; Dental Alloys; Dental Amalgam; Dental Bonding; Dental Caries; Dental Cavity Lining; Dental Enamel; Dental Materials; Dental Restoration, Permanent; Glass Ionomer Cements; Hardness; Humans; Molar; Phosphates; Resin Cements; Resins, Plant; Tooth Demineralization